Students’ Learning Styles in English Online Classes: A Case Study - Rama Theola Putra Mairanata, Heronimus (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
Online classes are a solution in education during the COVID-19 pandemic. The change from offline to online classes brings changes to the way students learn. This paper aims to explore English Department students’ learning styles in English online classes. The qualitative descriptive method is applied. The findings show that the student’s learning style applies multimodal modality preference. However, multimodal modality preference in the students’ combination of learning styles also shows a tendency to rely on single modal preference.  This denotes the students’ dominant learning style. It can be concluded that online classes support student learning styles without changing the students’ dominant learning styles.  The implications of the findings denote the power of visual media in students’ learning process. This reinforces the use of media in advanced teaching-learning processes.